Species richness representation within protected areas is associated with multiple interacting spatial features. Issue 3 (7th December 2015) - Durán, América Paz; Inger, Richard; Cantú‐Salazar, Lisette; Gaston, Kevin J.
Abstract: Aim: To assess the relative effects of the spatial features of protected areas (PAs), and their interactions, on species richness representation. Location: Continental America and associated islands. Methods: We used a novel dataset comprising species richness estimates for amphibians, birds and mammals for more than 400 PAs in the Western Hemisphere. Using spatial tools and remote sensing imagery, we calculated four spatial features for each PA: size, shape index, fragmentation level and proximity to the closest PA. The relative effect size of both PA spatial features and environmental covariates on levels of species richness, and how they interact, were assessed using generalized mixed effect models. Results: Spatial features and environmental covariates explained about 61% of the variation in species richness within PAs, with the magnitude of the effect remaining similar among spatial features and taxonomic groups. While area had a positive effect on species richness, shape index and fragmentation had negative effects. Proximity had a significant positive effect only for mammals and a negative effect for all the taxa combined. PA spatial features showed significant interactions between them and with environmental covariates. Main conclusions: We provide the first empirical evidence for the combined and interactive effects of terrestrial PA spatial features on predicting species richness. Our results suggest that the spatial features of PAs have an important effect on species richness and while the magnitude of this effect varies across taxonomic groups, its direction is consistent. Additionally, we show that the effect of one spatial design feature can be amplified or attenuated by that of another. These findings contribute towards a better understanding of the effect of spatial features on the performance of PAs and therefore how best to enhance the spatial configuration of existing and future PAs.